2012
DOI: 10.1007/s12011-012-9512-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of a Food Program on the Micronutrient Nutritional Status of Argentinean Lactating Mothers

Abstract: This study was conducted to evaluate the impact of a food aid program (Plan Más Vida, PMV) on the micronutrient nutritional condition of lactating mothers 1 year after its implementation. The food program provided supplementary diets (wheat- and maize-fortified flour, rice or sugar, and fortified soup) to low-income families from the province of Buenos Aires, Argentina. A prospective, non-experimental study was carried out to evaluate the micronutrient nutritional status of lactating mothers (n = 178 at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
3
2
1
6
Order By: Relevance
“…Regarding vitamin A, results are comparable since the risk of vitamin A deficiency improved in both pregnant and lactating women. In the case of serum zinc levels, they did not improve after the intervention neither in this report nor in the previous one [11].…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Regarding vitamin A, results are comparable since the risk of vitamin A deficiency improved in both pregnant and lactating women. In the case of serum zinc levels, they did not improve after the intervention neither in this report nor in the previous one [11].…”
Section: Discussioncontrasting
confidence: 88%
“…Findings in this study are similar to those reported for lactating women after PMV implementation [11]. In both cases, folic acid levels improved as a result of the implemented intervention.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding is comparable with studies from Kenya 25%, 13 Tanzania with 22% 12 and several studies in Ethiopia 22.1%, 11 28.3% 15 and 28.9%. 19 Our study was also similar to studies in Argentina and Nepal, with 25.8% 20 and 20%, 21 respectively.…”
Section: Discussionsupporting
confidence: 86%